La calidad del cuidado de Enfermería y el nivel de satisfacción de las necesidades espirituales en los pacientes del servicio de emergencia del Hospital José Agurto Tello, Lurigancho, Chosica, 2012 - Quintana Damián, Carmen (2019)
The aim of the study was to determine the relationship between the quality of nursing care and the level of satisfaction of the spiritual needs of patients in the Emergency Department of Hospital José Agurto Chosica Tello. Quantitative study, descriptive correlational because variables associated with a predictable pattern for a group or population.Cross cutting. We used non-probability sampling, as inclusion criteria, which were: adult male and female patientshospitalized in the emergency room and nurses working in the emergency room, taking a sample of 40 patients and40 nurses. By chi square test of independence is concluded that there is no relationship of partnership between thequality of nursing care and the level of satisfaction of the spiritual needs of patients in terms of (a) sense of belonging, love and respect , (b) the Divine, (c) positivity, gratitude, hope and peace, (d) the meaning and purpose of life,(e) morality and ethics, (f) recognition of beauty and (g) resolution before death . Concluding the more efficient isthe quality of care the nurse does not influence the level of satisfaction of patients’ spiritual needs. This does notmean that the nurse should provide quality spiritual care to the patient.